Klasifikasi Pemenuhan Pilar Sanitasi Puskesmas Menggunakan Metode Naive Bayes - Syam, Muhammad Farhan; Hayati, Lilis Nur; Syafie, Lukman (Komputika : Jurnal Sistem Komputer, 2023)
Sanitation is an attempt to maintain the cleanliness and condition of the surrounding environment. In fulfilling the sanitation pillar in each region, of course we also need the role of health agencies to trigger and provide education. In the village where the scope of the Bontomangape Health Center is located, it is known that the fulfillment of the sanitation pillar is still uneven. Based on this, the author intends to classify the fulfillment of the sanitation pillars of the puskesmas using the Naive Bayes method so that the results of this classification can be used as a benchmark for villages that need to be prioritized by sanitation workers. The classification results obtained were 55 implemented and 20 not implemented for Bontomangape village, 70 implemented and 5 not implemented for Campagaya village, 60 implemented and 15 not implemented for Kalenna village, 45 implemented and 30 not implemented for Parambambe village, 52 implemented and 23 not implemented implemented for Parangmata village, 64 implemented and 11 not implemented for Parasangangberu village, and 57 implemented and 18 implemented for Pattinoang village. The classification results obtained an average accuracy value of 95,81%, a precision value of 94,78% and a recall value of 100%. Keywords – Sanitation; Health; Puskesmas; Classification; Naive Bayes